Does Distal Radio-ulnar Joint Configuration Affect Postoperative Functional Results after Ulnar Shortening Osteotomy? - Fabian Gilbert, MD; Rafael G. Jakubietz, MD; Rainer H. Meffert, MD; Michael G. Jakubietz, Priv- Doz, MD (Plastic and Reconstructive Surgery, Global Open, 2018)
Background:. Reverse oblique distal radio-ulnar joint (DRUJ) configuration is assumed to show inferior postoperative results in ulnar-shortening osteotomy due to osteoarthritis, as the joint force pressure in the DRUJ may be increased. An evaluation and comparison of the postoperative functional results with regard to clinical and radiographic signs of arthritis among different DRUJ configurations was carried out retrospectively. Methods:. Sixty-two patients after ulnar shortening osteotomy were included. The minimum follow-up was 5 years. Preoperative x-rays were assessed for the DRUJ configuration according to the Tolat classification, whereas postoperative radiographs were evaluated with regard to signs of osteoarthritis using the Kallgren-Lawrence-Score. Functional results were evaluated using the disabilities of the arm, shoulder and hand (DASH) and Mayo Wrist Score and measuring range of motion and grip strength. Results:. Significantly better functional results were found in patients with parallel configuration of the DRUJ (Tolat type 1 configuration) with regard to DASH score, grip strength, and supination compared with nonparallel configurations. In the Tolat type 1, configurated DRUJ mean DASH score was 9 compared with 18 in the Tolat type 2 and 3 groups. Apart from supination, no differences were observed in range of motion among groups. Conclusion:. Although long-term postoperative range of motion failed to display statistically significant differences between DRUJ configurations except for supination, better results regarding grip strength and DASH scores were seen in a parallel-aligned DRUJ configuration. Although onset of osteoarthritis does not seem to become apparent within the observation period, nonparallel aligned configuration predisposes to inferior results.